2013
DOI: 10.1111/jpi.12106
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin prevents pancreatic β‐cell loss due to glucotoxicity: the relationship between oxidative stress and endoplasmic reticulum stress

Abstract: Prolonged hyperglycemia results in pancreatic β-cell dysfunction and apoptosis, referred to as glucotoxicity. Although both oxidative and endoplasmic reticulum (ER) stresses have been implicated as major causative mechanisms of β-cell glucotoxicity, the reciprocal importance between the two remains to be elucidated. The aim of this study was to evaluate the differential effect of oxidative stress and ER stress on β-cell glucotoxicity, by employing melatonin which has free radical-scavenging and antioxidant pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 76 publications
2
32
0
Order By: Relevance
“…And melatonin has been illustrated to have the antioxidant and anti-apoptosis properties in various cell types (Carpentieri et al, 2014;Park et al, 2013;Wang et al,2013). In the present study, we demonstrated that the preadministration of melatonin markedly attenuated Hy/SDinduced MSC early apoptosis/necroptosis supported by changes in cell viability and Annexin V/PI double staining assay, as well as the morphological changes.…”
Section: Discussionmentioning
confidence: 56%
“…And melatonin has been illustrated to have the antioxidant and anti-apoptosis properties in various cell types (Carpentieri et al, 2014;Park et al, 2013;Wang et al,2013). In the present study, we demonstrated that the preadministration of melatonin markedly attenuated Hy/SDinduced MSC early apoptosis/necroptosis supported by changes in cell viability and Annexin V/PI double staining assay, as well as the morphological changes.…”
Section: Discussionmentioning
confidence: 56%
“…Together, these data suggest that melatonin can have both stimulatory and inhibitory influences on insulin secretion. Notably, in vitro melatonin administration protects beta cells from the deleterious effects of glucose toxicity, improving beta cell survival, and reducing oxidative stress responses in both INS-1 832/13 rodent beta cells and isolated human islets from individuals with type 2 diabetes [115,116]. In vivo, chronic treatment with melatonin (10 mg kg −1 day −1 ) was also able to partially restore beta cell mass in a rat model of streptozotocin (STZ)-induced diabetes [117].…”
Section: The Pancreatic Response To Melatoninmentioning
confidence: 99%
“…Park et al. induced glucotoxicity in rat insulinoma INS‐1 cells to explore the protective mechanisms of melatonin. They observed that melatonin restored cell survival, decreased ROS production, and downregulated pro‐apoptotic protein expression (p38, JNK) and markers of apoptosis including caspase‐3 under high glucose conditions; moreover, the glucotoxic state caused a significantly reduction in the antioxidant defense system, but the addition of melatonin re‐instated this machinery.…”
Section: Melatonin In Other Pathophysiological Conditionsmentioning
confidence: 99%